2009
DOI: 10.3171/2008.4.17536
|View full text |Cite
|
Sign up to set email alerts
|

Independent association of extent of resection with survival in patients with malignant brain astrocytoma

Abstract: In the authors' experience with both primary and secondary resection of malignant brain astrocytomas, increasing extent of resection was associated with improved survival independent of age, degree of disability, WHO grade, or subsequent treatment modalities used. The maximum extent of resection should be safely attempted while minimizing the risk of surgically induced neurological injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
463
3
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(514 citation statements)
references
References 42 publications
17
463
3
21
Order By: Relevance
“…Extent of surgical resection, timing for adjuvant radiotherapy and indication of chemotherapy for hemispheric LGG are aspects of clinical management, which remain controversial. Small study size, heterogeneity of inclusion criteria, distinct demographic series and different histological types of tumor were some of the confounding parameters preventing a consensus on the optimal therapeutic approach in this patient group 4,13,16 . A retrospective review of 216 patients with hemispheric LGG, including volumetric analysis of the extent of surgical resection, has shown that patients with at least 90% resection had 5-and 8-year OS of 97 and 91%, respectively, whereas patients with less than 90% resection had 5-and 8-year OS rates of 76 and 60%, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extent of surgical resection, timing for adjuvant radiotherapy and indication of chemotherapy for hemispheric LGG are aspects of clinical management, which remain controversial. Small study size, heterogeneity of inclusion criteria, distinct demographic series and different histological types of tumor were some of the confounding parameters preventing a consensus on the optimal therapeutic approach in this patient group 4,13,16 . A retrospective review of 216 patients with hemispheric LGG, including volumetric analysis of the extent of surgical resection, has shown that patients with at least 90% resection had 5-and 8-year OS of 97 and 91%, respectively, whereas patients with less than 90% resection had 5-and 8-year OS rates of 76 and 60%, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this long survival time, 50-75% of these patients die as a result of either tumor recurrence or malignant progression 6,11 . Whereas expectant management was once acceptable, current trends and mounting evidence now favor more active management, including extensive surgical resection [12][13][14][15] . Nevertheless, studies tend to compare survival in good surgical candidates (especially those with tumors in non-eloquent brain areas) with survival in poor surgical candidates (with diffuse infiltrating tumors in eloquent brain areas)…”
Section: Low-grade Astrocytoma -Surgical Outcomes In Eloquent Versus mentioning
confidence: 99%
“…-тотальная: при отсутствии контрастного усиле-ния для опухолей, накапливающих контраст; -почти тотальная: при удалении более 90 % опухоли; -субтотальная: при удалении менее 90 % опухо-ли [7,14].…”
Section: Introductionunclassified
“…Many other authors also believe that the total removal of GBM may influence the survival. 6,12,13,15,19 McGirt et al 13 analyzed 451 GBM patients and had 13 months of average survival of those submitted to the total resection. However, other authors did not find any relation between total removal and survival.…”
Section: Modifiable Prognostic Factorsmentioning
confidence: 99%
“…12 According to several authors, age, the Karnofsky Performance Status (KPS), tumor removal and radiotherapy influence the patients' survival. 9,10,11,13,19 This study aims to observe if the GBM prognostic factors previously mentioned may have influenced our patients' survival.…”
Section: Introductionmentioning
confidence: 99%